Utricularia biceps (Lentibulariaceae), a new carnivorous species endemic to the campos rupestres of Brazil - Gonella, Paulo Minatel; Baleeiro, Paulo César (Phytotaxa, 2018)
Utricularia biceps (Lentibulariaceae), a new species belonging to U. sect. Foliosa, is here described and illustrated. This new species is endemic to the campos rupestres of eastern Brazil, an extremely biodiverse and endangered vegetation. Notes on phenology, ecology, habitat, and conservation are provided, along with a discussion on the features that distinguish this species from the other taxa of the genus. The recent discovery of this and many other new species in the Botumirim region, in northern Minas Gerais, highlight this area as a priority for biodiversity conservation and emphasize the importance of extensive studies on the flora of the region.